THE EXTANDING OF ECONOMIC-COST MODEL OF INFORMATION SECURITY RISKS MANAGMENT BY THE USE OF SOCIAL-PSYCHOLOGICAL TYPES OF INTRUDERS - Архипов, Олександр Євгенійович; Скиба, Андрій Володимирович; Хоріна, Олена Іванівна (Ukrainian Information Security Research Journal, 2015)
In this article we study the socio-psychological characteristicsof the attacker and their use with economic-costmodel for assessing information risks and optimal investmentin information security. An adequate assessmentof information risk and determining the optimal investmentby existing economic and cost models require expansionwith the socio-psychological characteristics of theattacker, which significantly affect the assessment of therisks. Modern methods of estimation of information risks,which are based on existing legal documents doesn’t takeinto account the socio-psychological characteristics of theattackers, leading to incorrect assessment, reducing itsaccuracy. The proposed expansion of economic-costmodel, taking into account the socio-psychological characteristicsof the attacker, which increases the risk assessmentof information and optimize investment in informationsecurity. We present 10 socio-psychologicaltypes of attacker for using with economic-cost modelswhich allows to expand the use and improve the accuracyof estimates of economic-cost model in the evaluation ofinformation risks.